2021
DOI: 10.1111/rego.12395
|View full text |Cite
|
Sign up to set email alerts
|

Private authority and public policy interactions in global context: Governance spheres for problem solving

Abstract: Private organizations play a growing role in governing global issues alongside traditional public actors such as states, international organizations, and subnational governments. What do we know about how private authority and public policy interact? What are the implications of answering this question for understanding support for, and effects of, policy development generally? The purpose of this article is to reflect on these questions by introducing, and reviewing, a special issue that challenges explicit c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 84 publications
2
62
0
1
Order By: Relevance
“…Clearly, there was great orchestration and support by the US government for the Alliance. Together with the Accord, we see clear endorsement by public authoritieswhat Cashore et al (2021) term coordinationfor the PG stemming from their domestic contexts, which fueled the institutionalization of PG in their respective environments. This finding is also consistent with other studies of international PG, which found that public authorities play a hugely influential role in encouraging and shaping domestic PG (Bartley 2003;Overdevest & Zeitlin 2016).…”
Section: Endorsement Of Domestic Rootsmentioning
confidence: 86%
See 1 more Smart Citation
“…Clearly, there was great orchestration and support by the US government for the Alliance. Together with the Accord, we see clear endorsement by public authoritieswhat Cashore et al (2021) term coordinationfor the PG stemming from their domestic contexts, which fueled the institutionalization of PG in their respective environments. This finding is also consistent with other studies of international PG, which found that public authorities play a hugely influential role in encouraging and shaping domestic PG (Bartley 2003;Overdevest & Zeitlin 2016).…”
Section: Endorsement Of Domestic Rootsmentioning
confidence: 86%
“…Other work has looked into broader institutions that influence firms' CSR, similarly finding a general congruence with prevailing institutions (Amable 2005;Witt & Redding 2012). Indeed, public authorities have begun to take a much more active role in shaping the PG forms and choices of actors (Cashore et al 2021;Marques & Eberlein 2021;Ponte et al 2020).…”
Section: National Contexts Csr and Pgmentioning
confidence: 99%
“…Drawing on theoretical advances from organizational studies, institutional logics expose interests and priorities specific to each sector, although public-private interactions remain widespread and difficult to classify. Cashore et al (2021) distinguish between these complex and diverse forms of public-private interactions, from coordination and collaboration to substitution and co-optation. Structurally-embedded hybridity is thus different from an instance of delegation from public to private actors, or a functional replacement of the latter by the former.…”
Section: Theoretical Insights: Hybridity and Ai Governancementioning
confidence: 99%
“…Some scholars have identified pathways depending on the degree to which public and private governance remain independent (public takeover, symbiotic, and hybrid pathways), while others have focused on cooperative and competitive interactions based on whether public and private rules or goals are compatible (Levin et al 2009;Cashore et al 2011;Eberlein et al 2014;Renckens 2015;Tosun et al 2016;Green & Auld 2017). In the introductory article to this special issue, Cashore et al (2021) distinguish between complementary, competitive, and coexistence interactions. While in complementary interactions public and private governance actors directly cooperate or operate to achieve similar goals, in competitive interactions the relationship is more antagonistic and combative.…”
Section: Transnational Private Governance and Public Regulatory Interventionsmentioning
confidence: 99%
“…While transnational private governance has emerged over the past three decades in a wide variety of sectors and issue areas, the literature on public-private governance interactions is still in development. 1 This article builds on this special issue's introductory article by Cashore et al (2021) to better understand these interaction dynamics in cases of public interventions in transnational private governance, such as eco-certification schemes. Private governance does not operate in a regulatory or jurisdictional vacuum.…”
Section: Introductionmentioning
confidence: 99%